La recreación infantil para fortalecer la autoestima de las niñas y niños de 4 a 5 años de edad del nivel inicial II de la escuela de educación básica Dr. Reinaldo Espinosa Aguilar de la ciudad de Loja. Periodo 2014-2015 - Vásquez Quizhpe, Angélica Catalina (2016)
This research includes a study on children's recreation to strengthen the self-esteem of children of 4-5 years of Initial level II school for Basic Education Dr. Reinaldo Espinosa Aguilar of the City of Loja. Period 2014-2015 The overall objective is focused to contribute to the development of self-esteem in children through child recreation. The methods that were present in the research are: scientific, analytical, hermeneutical, statistician. The technique I used was observation and the instrument applied was a Guide to the Children's Self-Esteem Rating aimed at children, the population studied was 13 children. The results obtained after applying the guidance for assessing the esteem we have 7 children corresponding to 38 % have acceptable esteem and 6 children corresponding to 77 % have low self esteem therefore concludes that it must perform activities help develop the recreational recommending that in order to strengthen the self-esteem of children self-esteem activities are conducted